PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN (PADA KUD PAKIS KEC. PAKIS KAB. MALANG) - Erda Mulidya; Hadi Sunaryo; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study aims to determine the influence of leadership, work environment and communication to employee job satisfaction. The research sample in this study amounted to 42 people who were employees of KUD (Village Unit Cooperative) PAKIS Kec. Pakis Kab. Malang.The method used is descriptive data analysis that is by using validity, reliability, normality, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, t hypothesis test, and hypothesis testing f.The results of this study indicate that partially each of the variables of leadership, work environment and communication are equally influential on job satisfaction, while simultaneously leadership, work environment and communication variables also influence job satisfaction of KUD (Village Unit Cooperative) PAKIS employees. Pakis Kab. Malang. Keywords: Leadership, Work Environment, Communication, Job Satisfaction